On odd mean graphs - Seoud M.A.; Salim M.A. (Utilitas Mathematica, 2011)
We prove that every odd mean graph is k-odd mean graph, and we put two necessary conditions on the graph to be an odd mean graph, then we determine all odd mean graphs of order ≤ 6.